A retrospective cross-sectional study of therapeutic results of single port thoracoscopy in patients with lung collapse due to trauma: comparison of entirely recovered and re-thoracoscopy needed patients - Mojtaba Ahmadinejad; Hedieh Soltani; Mojtaba Foroohi; Nafiseh Yousefi Manesh; Hooravash Mohajerani; Izadmehr Ahmadinejad; Javad Zebarjadi Bagherpour (BMC Surgery)
Abstract Introduction Lung collapse can occur for various reasons, especially trauma. Single-port thoracoscopy is a treatment method that has not been discussed in detail. This study aimed to investigate the results of single-port thoracoscopy as a treatment for trauma-induced lung collapse. Methods This descriptive retrospective cross-sectional study included 100 patients with lung collapse following trauma who were referred to the Madani Hospital. Demographic data, underlying causes and injuries, respiratory and consciousness state, pain level, recurrence rate, hospitalization period, complications, and narcotic and non-narcotic analgesics, re-thoracoscopy, and thoracotomy requirements were evaluated. Results The mean age of patients was 38 ± 16 years, and 65% were male. Single port thoracoscopy has suitable therapeutic effects, low complications, less pain, and reduced need for painkillers. Patients with more concomitant injuries, longer duration from trauma to performing thoracoscopy, intubation requirement, bilateral lung involvement, and lower GCS, required re-thoracoscopy, which has been associated with more extended hospitalization, suffering from more pain, need to receive narcotics and thoracotomy, and frequency of narcotic and non-narcotic agents. These results demonstrate the efficacy of the single port thoracoscopy in uncomplicated and initially completely recovered patients, and the re-thoracoscopy requirement and complications are based on the underlying cause and medical circumstances. Conclusion Single port thoracoscopy is practical for improving the quality of management of patients with lung collapse following trauma. Future studies should compare different methods.